1995
DOI: 10.1136/oem.52.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral median and ulnar neuropathy at the wrist in a parquet floorer.

Abstract: Many cases of work related compression neuropathy of the ulnar and median nerves at the wrist have been described. This report presents a case of bilateral distal neuropathy of the median and ulnar nerves in a parquet floorer, who laid wooden block flooring by hand and used the palms and volar surface of both hands to hit the blocks into place. He also used an electric sander and polisher. Bilateral numbness and paraesthesias in all fingers had been present for about one year. Clinical examination was normal; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, Web of Science and UpTodate was used. We included thirteen original studies that addressed the topic of work and ulnar neuropathy [ 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In addition, a review was included [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Web of Science and UpTodate was used. We included thirteen original studies that addressed the topic of work and ulnar neuropathy [ 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In addition, a review was included [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Rogier reported that while stationary working was a risk factor for cubital tunnel, working with the wrist at full extension or static working and work that necessitates loading with more than 1 kg for more than 10 times in an hour were risk factors for radial nerve entrapment. In a case of a floor parqueting worker who was required to perform repetitive hand movements, bilateral carpal tunnel syndrome at the Guyon's canal was reported, in addition to ulnar nerve entrapment [18].…”
Section: Discussionmentioning
confidence: 99%